PTH [1‐34]‐induced alterations predispose the mandibular condylar cartilage to mineralization. (June 2017) - Dutra, E. H.; O'Brien, M. H.; Gutierrez, T.; Lima, A; Nanda, R.; Yadav, S.
Structured Abstract: Objective: To study the effects of intermittent parathyroid hormone (PTH [1‐34]) on the mandibular condylar cartilage (MCC) and subchondral bone in adult female mice. Materials and Methods: Twenty‐two, 20‐week‐old female mice were used for in vivo experiments. The experimental mice (n=11) received daily intraperitoneal injections of PTH [1‐34] for 3 weeks, while control mice (n = 11) received intraperitoneal injections of 0.9% saline solution. Mice were euthanized and then micro‐computed tomography (micro‐CT); histology and immunostaining were carried out to assess the response. Results: Intermittent PTH [1‐34] led to early MCC breakdown and surface irregularities. Micro‐CT analyses indicated that PTH [1‐34] treatment led to increased bone volume fraction, tissue density and trabecular thickness, while decreasing the trabecular spacing. Histological analyses showed decreased proteoglycan secretion, increased bone turnover (TRAP staining) and increased mineralization. Furthermore, PTH [1‐34] treatment showed increased apoptosis of the cells. Our immunohistochemistry showed increased expression of pSMAD158 in the MCC and subchondral bone with PTH administration, whereas sclerostin (SOST) expression was decreased. Conclusions: Intermittent PTH [1‐34] results in early mineralization of the MCC, which may result in cartilage degeneration. Our results identified a novel mechanism by which PTH [1‐34] induces alteration in the microarchitecture of the MCC and the subchondral bone.